PENGARUH KEPEMIMPINAN, BUDAYA KERJA, LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA DAN KINERJA PERSONIL POLDA RIAU (Jurnal Tepak Manajemen Bisnis, 2014)
Abstract. The purpose of the study was to determine the effect of simultaneous and partial as well as the mostdominant of the factors of leadership, work culture and work environment on the performance of personnelthrough work discipline Riau Police personnel. Collecting data using a questionnaire that was distributed to100 personnel as respondents with a proportional approach and purposive sampling. The primary analysis ofthe study data with the two-stage regression based factor scores in factor analysis, in addition to descriptiveanalysis.The results show, hasa very high work performance and discipline, and have very good leadership factors, workculture, and work environment. Taken together, leadership, work culture and work environment significantlyaffect labor discipline, butin the category of weak predictive ability.This is because the only significant leadershipas well as the positive influence of the most dominant.But the culture and working environment indicates its roleindirectly to the work discipline, through leadership. While labor discipline have a major positive effect andsignificant impact on personnel performance.In addition,the results also indicate no significant leadership,culture and work environmentt directly affects the performance of personnel in Riau Police.Keywords: Leadership and Discipline Working Police Personnel of Riau.